Analisis Sikap Sosial Peserta Didik Terhadap Nilai Kearifan Lokal Malomang Pada Pembelajaran IPS Di SD - Aqilla F, Aqnessa; Lasari, Yufi Latmini (Jurnal Riset Madrasah Ibtidaiyah, 2024)
The application of local wisdom in learning in the independent curriculum as forming students' social character needs to be done well. This research aims to analyze students' attitudes towards Malomang local wisdom in social studies learning in elementary schools in Lima Pemuda District. The research method used was quantitative descriptive research, with participants being a number of elementary school students in five groups. Data collection was carried out through distributing questionnaires and structured interviews to randomly selected participants. The research questionnaire shows that the malomang tradition in Lima Kaum District gives rise to the phenomenon of social attitudes that influence the social attitudes of elementary school-age students in everyday life. Local wisdom values have obstacles in the implementation process. Several factors that influence the application of Malomang local wisdom include a lack of understanding of local wisdom, a lack of support from the surrounding environment, and a lack of experience in applying local wisdom in everyday life. Based on these findings, it is recommended that efforts be made to increase students' understanding and experience of local wisdom, such as through thematic learning that integrates local wisdom and involves the surrounding environment in the learning process. In this way, students can learn the value of local wisdom in character formation which is the aim of implementing the independent curriculum.